Synergism of Linezolid and Rifampin to Combat Multidrug-Resistant Environmental Enterococci Isolates - Mobina Noori; Leila Fozouni; Ania Ahani Azari (Tehran University of Medical Sciences, 2022)
Background and Aim: Wastewater is one of the most dangerous and important sources of pathogens and their treatment does not always guarantee the elimination of pathogenic bacteria. Enterococci, as opportunistic pathogenic bacteria, fastidious and cause of nosocomial infections, have a wide environmental distribution and one of the routes of their transmission to humans is water and wastewater. The increasing rate of drug- resistance among bacteria indicates the need for investigation of novel antibacterial agents or their combination effects. The aim of this study was to investigate the effect of linezolid in combination with rifampin on the elimination of multidrug- resistant enterococci in two treatment plants in Golestan province.  Materials and Methods: Enterococcus species from eighty samples were isolated from treatment plants in two cities of the Golestan Province (North of Iran) including Gorgan and Bandar-e Torkaman during January-June 2021. The isolates were identified based on the most probable number (MPN), filtration, microbiological tests and finally by using specific gene detection by ddlE primer with polymerase chain reaction. Kirby Bauer performed an antibiotic resistance pattern according to CLSI- 2020 guidelines for six classes of antibiotics. The minimum inhibitory concentration of linezolid was determined individually and by synergist effect with rifampin by broth microdilution method.  Results: After phenotypic and molecular diagnosis (PCR) of raw and treated wastewater samples, in 32 (40%) wastewater samples, enterococci species were identified and confirmed. Tetracycline was the least effective so, about 100% of Enterococcus faecalis and Enterococcus faecium isolates were resistant to it. The prevalence of linezolid-resistant E. faecalis was 11%. A total of 20 enterococcal isolates (62.5%) had multiple resistance. The concentration of linezolid in combination with rifampin, which inhibited 90% growth of the isolates (MIC90) was 1μg /ml, four-fold lower than linezolid alone (MIC90=4 μg/ml). In addition, none of the enterococci isolates showed resistance to the linezolid/rifampin combination (P=0.001). Conclusion: The results of this research confirmed the presence of enterococci resistant to vancomycin and other antibiotics in the wastewater treatment plant samples in Golestan province. The favorable combination effect of linezolid and rifampin on the inhibition of multi-drug resistant isolates implies their synergy.